2021
DOI: 10.1007/s00376-021-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Forward Operators for Simulation and Assimilation of Polarimetric Radar Data with Numerical Weather Predictions

Abstract: Many weather radar networks in the world have now provided polarimetric radar data (PRD) that have the potential to improve our understanding of cloud and precipitation microphysics, and numerical weather prediction (NWP). To realize this potential, an accurate and efficient set of polarimetric observation operators are needed to simulate and assimilate the PRD with an NWP model for an accurate analysis of the model state variables. For this purpose, a set of parameterized observation operators are developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The polarimetric radar variables for all species are computed using Equations 9-12 from Mahale et al (2019) for rain and Equations 7-10 above for all other species. Subsequently, the final variables for a grid box containing multiple species are obtained through summation across all species, following Equations 22-25 provided by Zhang et al (2021).…”
Section: Parameterized Polarimetric Radar Forward Operators (Pfos)mentioning
confidence: 99%
See 3 more Smart Citations
“…The polarimetric radar variables for all species are computed using Equations 9-12 from Mahale et al (2019) for rain and Equations 7-10 above for all other species. Subsequently, the final variables for a grid box containing multiple species are obtained through summation across all species, following Equations 22-25 provided by Zhang et al (2021).…”
Section: Parameterized Polarimetric Radar Forward Operators (Pfos)mentioning
confidence: 99%
“…PFOs are a set of parameterized relations between the polarimetric radar variables and the model state parameters, which are derived through scattering calculations and fitting procedures. The PFOs used in this study were developed and documented in Zhang et al (2021), which are summarized as follows.…”
Section: Parameterized Polarimetric Radar Forward Operators (Pfos)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhang et al [53] (hereafter Z21) developed a new set of simplified and parameterized PRD observation operators which can link NWP model state variables and PRD for DA use, and verified its validity and applicability by applying an ideal case and a real case respectively. They found that the parameterized operators yield results consistent with that of rigorous calculation in J10.…”
Section: Introductionmentioning
confidence: 99%